2020
DOI: 10.1039/d0cy01251c
|View full text |Cite
|
Sign up to set email alerts
|

Cascade transformations of (±)-citronellal to menthol over extruded Ru-MCM-41 catalysts in a continuous reactor

Abstract: Cascade transformations of ()-citronellal in a continuous mode was investigated over a bifunctional shaped ruthenium catalyst bearing metal clusters of the size 7 - 13 nm. Four types of Ru/H-MCM-41...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…These operations resulted in a partial blockage of the micropore mouths, lower micropore volumes and grain boundary interactions between H-MCM-41 and the Bindzil binder. This is in line with the literature 7,20–22,27–33 and SEM analysis (Fig. 3).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These operations resulted in a partial blockage of the micropore mouths, lower micropore volumes and grain boundary interactions between H-MCM-41 and the Bindzil binder. This is in line with the literature 7,20–22,27–33 and SEM analysis (Fig. 3).…”
Section: Resultssupporting
confidence: 93%
“…Extrusion in practice is done from suspensions containing various additives (binders, porogens, rheology improvers, peptizers, etc). The strategy for catalyst preparation by extrusion, adopted by the authors previously, 20 included along other recipes, preparation of a mechanical mixture of the binder and the catalytic phase by mechanical mixing, drying, calcination and grinding. This final mixture in a powder form, which already experienced mechanical impact leading to alteration of physico-chemical properties, underwent extrusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused our studies on six model compounds: vinyl acetate, coumarin, (−)-isopulegol, cinnamaldehyde, citronellal, and linalool, with some consideration of the fragrances eugenol, estragole, and benzaldehyde. The hydrogenation reactions of vinyl acetate, coumarin, cinnamaldehyde, citronellal, , and (−)-isopulegol , have been previously realized in continuous flow, but, to the best of our knowledge, never over additively manufactured catalysts or catalyst supports. We tested the hydrogenation of these six molecules over five sets of CSMs coated with one of four different metal catalyst species, namely palladium, platinum, ruthenium, and nickel.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for the hydrogenation step, the study from Nie et al, 2006 showed an increasing Ni loading from the Ni/BEA (Fatimah et al, 2015) catalysts that leads to faster hydrogenation and selectivity to produce menthol in a one-pot conversion. Particularly, the hydrogenation rate was insigni cantly in uenced by the increasing particle size, for example, in the Ru-deposited material on MCM-41 (Vajglová et al, 2020) , and Pt-Ga-MCM-41 (Balu et al, 2010) . The nanoparticles formed from active metals demonstrated a highly stable catalytic activity, as represented by better reusability (Balu et al, 2010;Fatimah et al, 2019).…”
Section: Citronellal Conversion Into Isopule-golmentioning
confidence: 99%